(untitled) (Bangladesh Journal of Medical Science, 2025)
Background Breast cancer screening is essential for early detection and reducing mortality; however, hesitancy towards screening persists globally, particularly in low- and middle-income countries (LMICs). To further understand the psychological, cultural, and structural barriers we need to utilize the validated tools to measure screening hesitancy as the first step in improving participation rates in the future. Method This systematic scoping review uses the Arksey and O’Malley framework together with the PRISMA extension, to filter studies based on relevancy regarding breast cancer screening and analytical quality. Studies are pulled from academic databases such as PubMed, Scopus, Web of Science, and Google Scholar that include frameworks such as the Health Belief Model (HBM) and Knowledge Attitude Practice (KAP) that focus on psychological and behavioral factors. The studies are pulled from the past decade. Results This review identified numerous frameworks used around the globe for determining screening hesitancy. However, among the most developed countries, HBM and KAP were the most widely used frameworks. These tools have good measurements of psychometric factors, but their lack of cultural adaptation limits their application in more diverse environments, especially in LMICs. Conclusion The findings highlight there need to have a more culturally adaptive, and a high psychometric standard tool for measuring breast cancer screening hesitancy. In the future, research should focus on developing more adaptive tools and using digital platforms to increase accessibility. By addressing these gaps, public health strategies can better reduce screening hesitancy, enhance early detection, and improve health conditions worldwide. BJMS, Vol. 24 No. 04 October’25 Page : 1304-1328